Spiritual Intelligence and Self-Efficacy among Operational Staff of Qazvin\'s Medical Centers: A Path Analysis - Omid Khosravizadeh; Saeed Shahsavari; Bahman Ahadinezhad; Fahimeh Asili Ansari; Roohangiz Taheri; Shoayb Rafiei (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Self-efficacy and spiritual beliefs can be considered as strong motives for improving the quality of working. Due to the different job description and environment than other service sectors, medical centers need to pay attention to these factors. So, the present study is aimed at identifying the effect of spiritual intelligence components on self-efficacy among operational staff of Qazvin medical centers. Methods: The present research is a descriptive-analytical and cross-sectional study conducted in 2019. About 238 people were selected by stratified sampling out of the medical centers staff in Qazvin, Iran. Spiritual intelligence was measured by King's questionnaire including four dimensions, and self-efficacy was measured by Sherer's questionnaires including three dimensions. Primary data analysis was done by Pearson's correlation test in SPSS20 software, and path analysis was done by structural equation modeling in AMOS software with the significance level of 0.05. Results: There was a significant direct relationship between all dimensions of self-efficacy and spiritual intelligence except persistence in the face of adversity and consciousness expansion (P-value ˂ 0.01). All the relationships were significant in path analysis of the final model. Also, the fit indices including NFI = 0.901, RMSEA = 0.055, GFI = 0.923, and CFI = 0.913 suggest the good fitness of the final model. Conclusion: The managers of the studied hospitals can promote self-efficacy in clinical staff and improve their performance and behavior in service provision by psychological enrichment of the staff and raising their spiritual intelligence.